Apicomplexan cell cycle flexibility: centrosome controls the clutch - Chen, Chun-Ti (Trends Parasitol, 2015)
The centrosome serves as a central hub coordinating multiple cellular events in eukaryotes. A recent study in Toxoplasma gondii revealed a unique bipartite structure of the centrosome, which coordinates the nuclear cycle (S-phase and mitosis) and budding cycle (cytokinesis) of the parasite, and deciphers the principle behind flexible apicomplexan cell division modes.